Efektivitas Vaksin Human Papillomavirus Pada Anak Perempuan dalam Upaya Pencegahan Kanker Serviks - Sono, Rafa Habiba; Ratna Dewi Puspita Sari; Rika Lisiswanti; Ari Irawan Romulya (Medula, 2024)
With high mortality rates worldwide, cervical cancer is a major threat to women's health. The World Health Organization (WHO) has set a global strategy for elimination through HPV vaccination. Indonesia has implemented the HPV Immunization Introduction Program, including its implementation in the School Children Immunization Month, aimed at grade 5 and 6 elementary schools. The prevalence of cervical lesions has been reduced by HPV vaccination, but screening and adapting to changing epidemiology remain challenging. The influence of socioeconomic factors on risk highlights the need for prevention strategies that address social disparities. Successful vaccination not only protects individuals but also contributes to overall public health. Therefore, it requires adaptation and collaboration across sectors to address cervical cancer globally.